2015
DOI: 10.1155/2015/407654
|View full text |Cite
|
Sign up to set email alerts
|

Intoxication by Cyanide in Pregnant Sows: Prenatal and Postnatal Evaluation

Abstract: Cyanide is a ubiquitous chemical in the environment and has been associated with many intoxication episodes; however, little is known about its potentially toxic effects on development. The aim of this study was to evaluate the effects of maternal exposure to potassium cyanide (KCN) during pregnancy on both sows and their offspring. Twenty-four pregnant sows were allocated into four groups that orally received different doses of KCN (0.0, 2.0, 4.0, and 6.0 mg/kg of body weight) from day 21 of pregnancy to term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Cyanide has been established to cause kidney damage in different organisms. [30,31].The result from this present study is in agreement with these findings as renal toxicity was indicated by the recorded increase in creatinine and urea concentrations in the serum and kidney. However co-treatment with T. tetraptera restored the concentration of creatinine to near normal level.…”
Section: Discussionsupporting
confidence: 92%
“…Cyanide has been established to cause kidney damage in different organisms. [30,31].The result from this present study is in agreement with these findings as renal toxicity was indicated by the recorded increase in creatinine and urea concentrations in the serum and kidney. However co-treatment with T. tetraptera restored the concentration of creatinine to near normal level.…”
Section: Discussionsupporting
confidence: 92%
“…In 2016, 198 cyanide exposure cases were reported in the United States, of which, nearly 70% were unintentionally exposed and more than 8% were due to intentional poisoning [8]. Although accidental exposure to cyanide is primarily caused by consumption of the seeds and roots of certain plants [4,[9][10][11], it is commonly encountered in industrial workers who have access to cyanide salts [3,12] and in smokers and fire victims due to the inhalation of cyanide-containing smoke [13][14][15]. Confirmation of cyanide exposure is an important task for clinical diagnosis, workplace safety, environmental monitoring, and forensics.…”
Section: Introductionmentioning
confidence: 99%
“…Two major approaches are currently adopted for the detection of cyanide exposure from biological samples: 1) direct detection of cyanide and 2) detection of its major metabolite, thiocyanate. Direct cyanide detection can be performed both at the field and in the laboratory [1,6,12,[16][17][18]. However, the high volatility and short half-life (t 1/2 = 0.34 -1.28 hours) of cyanide narrow the detection window for successful analysis [19].…”
Section: Introductionmentioning
confidence: 99%
“…The study was designed to comply with U.S. EPA GLP standards (EPA, 2011a(EPA, , 2011b and guidance outlined in the OECD Test Guideline 408 (OECD, 2018) and EPA Health Effects Test Guideline OPPTS 870.3100 (EPA, 1998), with some minor exceptions. Twenty (20) male F344 rats per group were provided NaCN in drinking water for 13 weeks, followed by a 10-week recovery period.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in laboratory animals have also demonstrated that CN can cause necrotic and demyelinating lesions in the brain (Ibrahim, Briscoe Jr., Bayliss, & Adams, 1963) and optic nerves (Lessell, 1971) following bolus injections, but the dosage levels required to produce these effects were near or within the lethal range. In addition, studies in rats and pigs have shown disturbances in thyroid function (Daniel, Adekilekun, Adewale, & Adekemi, 2013; Gotardo et al, 2015). The effects associated with the subchronic administration of CN, however, are less clear.…”
Section: Introductionmentioning
confidence: 99%